Networked Carbon Markets : Design Options for an International Carbon Asset Reserve for the World - Fuessler, Juerg; Herren, Martin (World Bank, Washington, DC, 2015)
This paper presents first concepts and insights on an International Carbon Asset Reserve. In particular, it explores how different design options can support a range of networked carbon pricing efforts. The report provides an overview of key risks in carbon markets, highlights the benefits of pooling risks on an aggregated scale, and identifies potential design options and structures for an international carbon asset reserve. The paper contributes to the wide effort to promote a long-term price on carbon and carbon market stabilization, comparability, and networking.